Eco pot / Mogana Shree Anatha Raja, Thrivenraj Vimalathitan and Sadhna Pandian - Anatha Raja, Mogana Shree; Vimalathitan, Thrivenraj; Pandian, Sadhna (Universiti Teknologi MARA, Kedah, 2019)
Petroleum-based plastic nursery pots is convenient. They're lightweight, yet durable and most can be recycled or reused.. An estimated 31 million tons of plastic waste was generated in 2017, reports the Environmental Protection Agency. Only 8 percent of it was recycled, a disturbing figure when you consider the agency says it can take 100 to 4 00 years for plastic to break down in a landfill. Eco Pot is excellent for seeds starting transplants. Best of all, these pots are 100% natural and biodegradable. Completely biodegradable pots make seed starting easy transplant seedlings, pot and all, directly into garden, reducing transplant shock. Pots add nutrients to the soil as the degrade plants thrive in these pots. The manure is dried, completely composted, mixed with neem and pressed into pots. We use chopped neem leaves mixed with the cow dung. They last for months but will dissolve within weeks after planting in the garden, providing essential organic nutrients. Eco Pots produces healthier roots by air pruning and creating lots of smaller finger roots. These roots absorb moisture and nutrients more efficiently so your plant grows faster and stronger. An Eco Pot is an exciting high-performing alternative to plastic and peat pots. This pot will give you the benefits of manure and allowing roots to quickly expand and grow a stronger, healthier plant.